2010
DOI: 10.1016/j.jcat.2009.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in sorption and hydrogenation of methyl oleate and elaidate on MFI zeolites

Abstract: a b s t r a c tDifferent zeolites were tested for selective removal of methyl elaidate (trans isomer) from an equimolar mixture with methyl oleate (cis isomer). Sorption experiments of the geometric isomers show that only ZSM-5 samples with reduced Al content in the framework are able to discriminate among the bent cis and the linear trans fatty acid methyl esters. Hydrogenation experiments of equimolar methyl oleate and elaidate mixtures at low temperature (65°C) and high hydrogen pressure (6.0 MPa), using Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 41 publications
1
32
0
1
Order By: Relevance
“…The higherr ate of skeletal isomerisation with EA compared to OA suggests that the trans form is favoured for entry into the channels, and this is also intuitively expected as it has as maller molecular cross-section;s uch shape-selectives orption has been recently demonstrated in the preferential hydrogenationo fm ethyl esters of EA over OA. [52] Under our reaction conditions, even weakly acidic sites on the external catalyst surfacea re able to catalyset he initial isomerisation of OA to EA. However,i ti sn ot possible to determine whether cis/trans isomerisation is a prerequisite for the branching reaction, as it occurst oasignificant level at the reaction temperature even in the absence of any catalyst (exp.…”
Section: Catalytic Testingmentioning
confidence: 79%
“…The higherr ate of skeletal isomerisation with EA compared to OA suggests that the trans form is favoured for entry into the channels, and this is also intuitively expected as it has as maller molecular cross-section;s uch shape-selectives orption has been recently demonstrated in the preferential hydrogenationo fm ethyl esters of EA over OA. [52] Under our reaction conditions, even weakly acidic sites on the external catalyst surfacea re able to catalyset he initial isomerisation of OA to EA. However,i ti sn ot possible to determine whether cis/trans isomerisation is a prerequisite for the branching reaction, as it occurst oasignificant level at the reaction temperature even in the absence of any catalyst (exp.…”
Section: Catalytic Testingmentioning
confidence: 79%
“…[29] So beschrieb eine Patentanwendung bereits 1998 die selektive Entfernung von transFettsäuren aus teilhydrierten Fetten durch Chemokatalyse. [30] In diesem Fall katalysierten Pt-beladene Zeolithe die selektive Hydrierung von trans-Fettsäureketten im Triglyceridmolekül.…”
Section: Strategien Zur Selektiven Abtrennung Von Trans-isomerenunclassified
“…[150] During their studies on the hydrogenation of these oils by heterogeneous Pt catalysts, [151] the research groups of Jacobs and Sels found that zeolite-supported catalysts perform better than the corresponding alumina-supported promoters, in terms of both partial hydrogenation and regioselectivity. [150] During their studies on the hydrogenation of these oils by heterogeneous Pt catalysts, [151] the research groups of Jacobs and Sels found that zeolite-supported catalysts perform better than the corresponding alumina-supported promoters, in terms of both partial hydrogenation and regioselectivity.…”
Section: Other Processesmentioning
confidence: 99%